Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.jasms.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The structure of gas-phase bradykinin fragment 1–5 (RPPGF) ions: An ion mobility spectrometry and H/D exchange ion-molecule reaction chemistry study

Abstract: Ion mobility-mass spectrometry (IM-MS) data is interpreted as evidence that gas-phase bradykinin fragment 1-5 (BK1-5, RPPGF) [M ϩ H] ϩ ions exist as three distinct structural forms, and the relative abundances of the structural forms depend on the solvent used to prepare the matrix-assisted laser desorption ionization (MALDI) samples. Samples prepared from organic rich solvents (90% methanol/10% water) yield ions having an ion mobility arrival-time distribution (ATD) that is dominated by a single peak; conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 38 publications
2
64
0
Order By: Relevance
“…We assumed that protonation occurred on the guanidine group owing to the high proton affinity (PA ϭ 251.2 kcal/mol) for arginine [23], but we also considered whether the most stable structure of the [M ϩ H] ϩ ion is a charge-solvated species, as suggested by Simon et al [31], or zwitterionic species, as suggested by Strittmatter and Williams [28]. To address this question, we used a combination of collision cross-sections obtained by using ion mobility spectrometry (IMS) [45] [46]. Note also that the collision cross-section for [GR ϩ H] ϩ is larger than that for [RG ϩ H] ϩ , and the methyl esters exhibit the same ordering.…”
Section: Resultsmentioning
confidence: 99%
“…We assumed that protonation occurred on the guanidine group owing to the high proton affinity (PA ϭ 251.2 kcal/mol) for arginine [23], but we also considered whether the most stable structure of the [M ϩ H] ϩ ion is a charge-solvated species, as suggested by Simon et al [31], or zwitterionic species, as suggested by Strittmatter and Williams [28]. To address this question, we used a combination of collision cross-sections obtained by using ion mobility spectrometry (IMS) [45] [46]. Note also that the collision cross-section for [GR ϩ H] ϩ is larger than that for [RG ϩ H] ϩ , and the methyl esters exhibit the same ordering.…”
Section: Resultsmentioning
confidence: 99%
“…The ion mobility and H/D exchange of the nonapeptide bradykinin and related analogues have been extensively studied [10,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Ion mobility measurements have shown that the singly-and doubly-protonated ions of bradykinin have a similar cross-section, while the triplyprotonated ion has a cross-section that is approximately 15% larger, providing evidence for a much less compact structure [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase hydrogen/deuterium exchange of small oligonucleotides (dTG, dC 6 and C 6 ) with CD 3 0D was performed in the second hexapole of a Fourier transform ion-cyclotron resonance (FTICR) mass spectrometer. Ion activation experiments were conducted by accelerating the ions at the entrance of the H/D exchange cell under conditions promoting exclusively collisional isomerization.…”
mentioning
confidence: 99%
“…The rate of gasphase H/D exchange has been shown to be a function of the reagent used for exchange (nature and concentration), the charge state of the biomolecule, the gasphase basicity/acidity of exchangeable sites, and the internal structure of the biomolecular ions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Probing the number of exchanged hydrogens and the H/D exchange kinetics makes it possible to distinguish ion populations and to elucidate their structural and thermochemical features.…”
mentioning
confidence: 99%
See 1 more Smart Citation